2019
DOI: 10.1109/access.2019.2921088
|View full text |Cite
|
Sign up to set email alerts
|

X-Band Dual Circularly Polarized Patch Antenna With High Gain for Small Satellites

Abstract: This paper presents an X-band circularly polarized patch antenna with a simulated high gain of 12.5 dBi and a simulated side-lobe-level of below −20 dB, within the bandwidth of 5.2 %. This single element antenna achieves high gain by exploiting the mode superposition of TM 11 + TM 13 (excited by a circle of vias loading the cavity) and TM 12 + TM 14 (excited by the cavity itself) radiated from the two apertures, respectively. A simple feeding network, consisting of a quadrature hybrid and a couple of 90 • bent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Patch antennas have attracted lots of attentions benefiting from their superiorities of ease of fabrication, low profile, easy realization of circular polarization, good compatibility with microwave passive and active circuits, 19 etc. Square radiation patches 20‐22 or circular radiation patches 23 are excited with orthogonal feeding ports by employing quadrature couplers, forming dual‐CP radiation. A CPW transmission feeding line patch excited by even and odd mode ports realizes dual‐CP within a compact solution 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Patch antennas have attracted lots of attentions benefiting from their superiorities of ease of fabrication, low profile, easy realization of circular polarization, good compatibility with microwave passive and active circuits, 19 etc. Square radiation patches 20‐22 or circular radiation patches 23 are excited with orthogonal feeding ports by employing quadrature couplers, forming dual‐CP radiation. A CPW transmission feeding line patch excited by even and odd mode ports realizes dual‐CP within a compact solution 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In the open literature, many designs have utilized a branch line coupler as an effective method to achieve dual circular polarization [17][18][19][20][21][22]. The coupler ensures having two output signals equal in magnitude with 90° phase shift needed for CP generation.…”
Section: Introductionmentioning
confidence: 99%
“…Using a hybrid coupler as feeding structure, the antenna can provide either left-hand CP (LHCP) or righthand CP (RHCP) depending on the excited port. Although wide AR BW can be conveniently accomplished in [17][18][19][20][21][22] by this method, the most challenging aspect is the poor interport isolation. The literature review has found that the best performance in the operating BW is only about 15% [17] with isolation of better than 15 dB, where the radiating patch is coupled to the coupler through double H-shaped slots.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations